Management begins with you or me (Gestión y Gerencia, 2022)
From the underlying of epistemology and the sense of the ontology of being, this essay deals with an unpublished version of the sense of intelligence complemented with wisdom as relevant elements in comprehensive training from the cognitive to the philosophical. The science challenge adheres to a narrow view of intelligence, arguing that intelligence quotient (IQ) is a genetic factor that cannot be modified by life experience, and that our destiny in life is largely determined by these aptitudes, But the emotional architecture of the brain requires emotional intelligence: being able to restrain the emotional impulse, interpret the most intimate feelings of the other, handle relationships in a fluid way, according to Aristotle (quoted by Goleman, 1996) the rare possibility of "getting angry with the right person, at the right intensity, at the right time, and in the right way ”(p. 17). Statement that places emotions at the center of life skills.  We have the spiritual intelligence to face and confront the problems of evil and good, of life and death, the deepest origins of suffering and despair. We use IES to be creative, we turn to it when we need to be flexible, visionary. Wisdom, a refreshing breath, especially in these times, endless orientations to face spiritual combat, is the constant search, a philosophy of life, of inner, deep reunions ... it is mainly to know oneself, there it all starts.
Keywords: IQ; emotional intelligence; spiritual intelligence; wisdom-management